1993
DOI: 10.1002/ddr.430300102
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term potentiation and the mechanisms of memory

Abstract: Long-term potentiation (LIP) is a cellular model of the memory processes that occurs in many nerve cells, usually at glutamatergic synapses. For this reason, glutamatergic synapses being the most abundant in the brain, LTP has been widely proposed as a mechanism of memory. Recent findings support this proposal and indicate that, indeed, LTP and memory processes share many properties. The initial steps of LTP and of memory involve the activation of glutamatergic NMDA (N-methyl-D-asprtate) receptors, sensitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 128 publications
1
9
0
Order By: Relevance
“…When dosed only prior to the acquisition trial (T1) or the retention trial (T2), CX691 significantly attenuated the temporal deficit, suggesting that it is exerting its pro-cognitive effects by enhancing both acquisition and retention/retrieval of the information. This is consistent with literature suggesting that AMPA receptors might be involved in both acquisition and retrieval processes (Izquierdo 1993;Danysz et al 1995). By contrast, a previous study suggested that an alternative AMPA receptor positive modulator, S-18986, affected only retrieval processes when tested in this task (Lebrun et al 2000).…”
Section: Discrimination Trials To Criteriasupporting
confidence: 82%
“…When dosed only prior to the acquisition trial (T1) or the retention trial (T2), CX691 significantly attenuated the temporal deficit, suggesting that it is exerting its pro-cognitive effects by enhancing both acquisition and retention/retrieval of the information. This is consistent with literature suggesting that AMPA receptors might be involved in both acquisition and retrieval processes (Izquierdo 1993;Danysz et al 1995). By contrast, a previous study suggested that an alternative AMPA receptor positive modulator, S-18986, affected only retrieval processes when tested in this task (Lebrun et al 2000).…”
Section: Discrimination Trials To Criteriasupporting
confidence: 82%
“…Dunnett & Robbins [ 31] suggested that the dopaminergic system is related to visual processing and attention. Excitatory amino acid receptor agonists such as glutamate showed adverse effects: long‐term potentiation has been suggested to be the physiological correlate of memory formation [ 32]. On the other hand, high levels of glutamate are neurotoxic [ 33].…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus plays important roles in cognition and neuroendocrine function (13,19), and is known to be important for the consolidation of memories in different tasks, including the tasks studied in this report (27). It should be noted that while deleterious effects of excess glucocorticoid on the brain have been shown, there is little evidence indicating whether brain function itself is compromised in a situation of repeated stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many studies have provided evidence that glucocorticoids regulate learning and memory (5,(7)(8)(9)(10). It has also been shown that stress impairs hippocampal long-term potentiation (LTP) (11,12), a long-lasting increase in synaptic excitability that might be involved in the mechanism of memory storage (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation